Ultra-Small Silver Nanoparticles: A Sustainable Green Synthesis Approach for Antibacterial Activity - Javier Emanuel Castañeda-Aude; José Rubén Morones-Ramírez; David Alejandro De Haro-Del Río; Angel León-Buitimea; Enrique Díaz Barriga-Castro; Carlos Enrique Escárcega-González (MDPI AG, 2023)
The present study centers on the synthesis of ultra-small silver nanoparticles (AgNPs) with antibacterial properties using citrus peel residues (orange, lemon, and grapefruit) as reducing and stabilizing agents, and on assessing their antibacterial activity against multidrug-resistant clinical Staphylococcus aureus. The synthesized AgNPs were analyzed by various techniques, including UV-Vis spectroscopy, SAED, TEM, XRD, FTIR, and Raman. The results demonstrate the formation of ultra-small, monodisperse, quasi-spherical AgNPs with an average particle size of 2.42 nm for AgNPs produced with mixed extracts. XRD analysis indicated that the AgNPs have a crystal size of 9.71 to 16.23 nm. The AgNPs exhibited potent inhibitory activity against resistant S. aureus, with a minimum inhibitory concentration (MIC) of 15.625 to 62.50 ppm. The findings suggest that the ultra-small nanometer size of the AgNPs could be attributed to the synthesis method that employs ambient conditions and the presence of polyphenolic compounds from citrus peel. Consequently, AgNPs obtained through sustainable green synthesis hold significant potential in combating clinical multi-resistant bacterial strains that are challenging to treat and eradicate. This approach also contributes to the revaluation of citrus residues in the region, which is an ongoing environmental issue today.